STUDIES ON THE DETERMINATION OF THE CUMULATIVE PROPERTIES OF THE DRY EXTRACT "HELMINTH-ART" - Khabibullaevna, Yuldasheva Shahlo; Rakhmanovich, Tukhtaev Hakim (Journal of Medical Genetics and Clinical Biology, 2024)
The object of this study was the dry extract of "Helminth-ART". The cumulative properties of the anthelmintic dry extract "Helminth-ART" were studied in an experiment on mice. It was also found that it does not have cumulative properties.